DESAIN PEMASARAN DIGITAL, KEMASAN DAN LABEL PADA UMKM EMBAL IBU BAINA NEGERI YAPUTIH KECAMATAN TEHORU KABUPATEN MALUKU TENGAH - M. Faqih Fauzan Tehuayo; Dian Utami Sutiksno; Evandro A. W. Manuputty (P3M Politeknik Negeri Ambon, 2022)
Ibu Baina's embalming business does not have digital media marketing Facebook, Instagram, and is not even recorded on Google Maps. Packaging only uses ordinary plastic bags for products. the packaging used is not safe food grade for packing food/beverage products, does not have a packaging product label. the goal to be achieved is to carry out a marketing strategy